Dinamika Strutur Kepribadian Film “One Fine Day”, Kajian Psikoanalisis Freud terhadap Konflik Cinta Remaja - Dian Ayu Mardiana; Sabil Akmal Maulana; Resdianto Permata Raharjo; Indah Puspitasri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze the dynamics of adolescent love conflict in the film One Fine Day (2018), directed by Asep Kusdinar, through the lens of Sigmund Freud's psychoanalysis. The main focus of the study is the interaction of the three personality structures: the Id, Ego, and Superego, which shape the main characters' decision-making and behavior when facing romantic dilemmas. Using qualitative research methods with A content analysis approach, this study highlights how the characters Mahesa and Alana experience tension between impulsive drives (Id), demands of reality (Ego), and internalized moral norms (Superego). The results of this analysis indicate that the adolescent love conflict in this film is not merely a matter of superficial emotions, but rather a reflection of psychological struggles in the process of searching for identity. The film effectively visualizes how its characters negotiate desires, social rules, and moral principles, ultimately leading to character growth and emotional maturity. This study confirms the relevance of Freud's theory in understanding the psychological complexity of young people, especially as represented through cinema.